Development of an Open Hearth Furnace with a Mechanical Blower and Mechanized Bellow - Oluwasanmi Iyiola Alonge; Adebunmi Peter Okediji; Ismaila Olanrewaju Alabi; Adegbola David Adeniran (ABUAD Journal of Engineering Research and Development, 2025)
This study focuses on the development of a hearth furnace with a mechanical blower and mechanized bellow intended to replace traditional open-hearth furnaces with restricted operational efficiency. The bellow system utilizes a crank-slider mechanism powered by an electric motor to generate a continuous airflow, thereby optimizing combustion within the furnace. The total force acting on the crank-slider was 22.22 N, and the calculated stoichiometric air required for complete combustion of the charcoal was 26.80 . The maximum temperature recorded during performance evaluation was 110 5  for the blower with energy consumption of 940.8 kJ and 923.9  for the bellow with energy consumption of 24.4 kJ. The air speed achieved by the bellow was 3.5 m/s each time the bellow compresses, with reduced pulsating interval and enhanced combustion of the charcoal. Compared to manual operation, the furnace reduced human exposure to heat, eliminated operational fatigue, and improved the overall efficiency and safety of the furnace operation. The results demonstrate that integrating a mechanical blower and a mechanized bellow into open-hearth furnace systems is a viable method to boost production rates and occupational safety in small-scale foundry operations.